Attractive Dispersion Interactions Versus Steric Repulsion of tert‐Butyl groups in the Crystal Packing of a D3h‐Symmetric Tris(quinoxalinophenanthrophenazine). Issue 2 (2nd December 2015) - Kohl, Bernd; Bohnwagner, Mercedes V.; Rominger, Frank; Wadepohl, Hubert; Dreuw, Andreas; Mastalerz, Michael
Abstract: The crystalline packing of a π‐extended D 3 h ‐symmetric triptycene reveals a particular π stacking motif with an almost‐eclipsed arrangement of adjacent π planes despite the steric repulsion of tert ‐butyl substituents. Four model compounds were analyzed by using single‐crystal X‐ray diffraction and theoretical calculations to study the influence of dispersion interactions of molecular parts and understand the relationship between the molecular structure and this unique packing motif. Abstract : Eclipse all else : The particular π stacking motif in the crystal packing of a π‐extended D 3 h ‐symmetric triptycene, which reveals an almost‐eclipsed arrangement of the tert ‐butyl substituents (see figure), was investigated by using single‐crystal X‐ray diffraction and theoretical calculations for four model compounds